2020
DOI: 10.1785/0120200118
|View full text |Cite
|
Sign up to set email alerts
|

A Frequency-Dependent Model for the Shape of the Fourier Amplitude Spectrum of Acceleration at High Frequencies

Abstract: The high-frequency decay term of the acceleration spectrum κ is a commonly used parameter in engineering seismology. In recent years, the assumption of a linearly decaying spectrum in log–linear space has been recognized to not always be valid as the value of κ depends on the analyzed frequency band. We present an alternative model for the spectral falloff in which the frequency dependence is explicitly taken into account. This is motivated by observations that the quality factor Q has a power-law dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 48 publications
(65 reference statements)
1
52
0
Order By: Relevance
“…This simple parameterization of attenuation ignores any frequency dependence to Q (e.g. [106][107][108]), and also trade-off between geometrical spreading (different for different wave types) and attenuation, which is well known from empirical ground motion prediction modelling (e.g. [109][110][111]).…”
Section: X(t) = S(t) * G(t) * K(t) * I(t)mentioning
confidence: 99%
“…This simple parameterization of attenuation ignores any frequency dependence to Q (e.g. [106][107][108]), and also trade-off between geometrical spreading (different for different wave types) and attenuation, which is well known from empirical ground motion prediction modelling (e.g. [109][110][111]).…”
Section: X(t) = S(t) * G(t) * K(t) * I(t)mentioning
confidence: 99%
“…Our observations of site effects up to 200 Hz relate to poorly understood processes governing high-frequency attenuation which is typically modeled using the κ parameter in engineering seismology and ground motion studies (Anderson & Hough, 1984;Ktenidou et al, 2014). This parameter can be separated into having a path and a site contribution.…”
Section: Site Effectsmentioning
confidence: 98%
“…Alternative coda analysis methods to constrain source and medium effects equally consider narrow‐band envelopes (Holt et al., 2021; Mayeda et al., 2003, and others), but the advantages of the radiative transfer model are that it depends explicitly on the scattering medium properties, and resulting magnitudes do not require calibration. The shapes of the long seismograms constrain intrinsic or inelastic attenuation, in contrast to methods targeting the decay of the direct wave amplitude (Anderson & Hough, 1984; Boatwright, 1978). Therefore, both attenuation mechanisms can be inverted for separately, similar to multiple lapse time window analysis (Fehler et al., 1992; Hoshiba, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Negative κ r may result from (1) uncertainties in the computation procedure and (2) bias from site effects at high frequencies. The assumptions underlying Anderson and Hough (1984) classic κ r model require that the site response at high frequencies is almost flat (Haendel et al, 2020), which may fit the response of most local geologic structures appropriately. Due to limited subsurface characterization in our region of study, all sites with significant amplifications at high frequencies cannot be identified.…”
Section: Site Metadata For Californiamentioning
confidence: 99%